2012
DOI: 10.1021/ol303240a
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking Nature: Synthetic Nicotinamide Cofactors for C═C Bioreduction Using Enoate Reductases

Abstract: A series of synthetic nicotinamide cofactors were synthesized to replace natural nicotinamide cofactors and promote enoate reductase (ER)-catalyzed reactions without compromising activity or stereoselectivity of the bioreduction process. Conversions and enantioselectivities of up to >99% were obtained for C=C bioreductions and the process was successfully upscaled. Furthermore, high chemoselectivity was observed when employing these nicotinamide cofactor mimics (mNADs) with crude extracts in ER-catalyzed react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
197
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(206 citation statements)
references
References 38 publications
4
197
0
5
Order By: Relevance
“…Since then, many classical OYEs were identified from proteobacteria (NCR [84], MR [85], PETNR [8]), flavobacteria (Chr-OYE2 [74]), cyanobacteria [21], yeasts (OYE1-OYE3 [86,87], CYE [62]) and plants [67], outlined in Tables 1 and 2. Nicotinamide coenzyme biomimetics (NCBs) previously used in OYE-catalysed hydrogenations to replace NAD(P)H [52,55,58].…”
Section: Phylogenetic Classification Of Oyesmentioning
confidence: 99%
See 3 more Smart Citations
“…Since then, many classical OYEs were identified from proteobacteria (NCR [84], MR [85], PETNR [8]), flavobacteria (Chr-OYE2 [74]), cyanobacteria [21], yeasts (OYE1-OYE3 [86,87], CYE [62]) and plants [67], outlined in Tables 1 and 2. Nicotinamide coenzyme biomimetics (NCBs) previously used in OYE-catalysed hydrogenations to replace NAD(P)H [52,55,58].…”
Section: Phylogenetic Classification Of Oyesmentioning
confidence: 99%
“…A highly promising and elegant alternative is the use of relatively inexpensive nicotinamide coenzyme biomimetics (NCBs) [52][53][54][55][56]. The latter compounds retain the pyridine ring structure, substituted with varied functional groups either on the N1 nitrogen (NCBs 1-2, 6-7, Figure 1) or at the C3 carbon (NCBs 3-5) [55].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In chemical catalysis, Hantzsch ester (HEH) successfully acts as a reductant in the asymmetric hydrogenation of benzoxazinones 6 and another artificial cofactor 9,10-dihydrophenanthridine (DHPD) has been designed for the asymmetric hydrogenation of benzoxazinones, benzoxazines, quinoxalines and quinolones, resulting in excellent activities and enantioselectivities. 7 Moreover, a widely-used artificial cofactor BNAH has been reported to react with oxidoreductases such as enoate reductases for CQC bioreduction, 8 and horse liver alcohol dehydrogenase for chiral synthesis. 9 Most notably, Nigel et al reported the cocrystal structures of flavin-containing enzyme ene reductases (ERs) from the Old Yellow Enzyme family (EC 1.3.1.31) in complex with NADH and the representative artificial cofactor, validating that both natural and artificial cofactors shared a similar p-p stacking effect and occupied the same region of the active sites.…”
mentioning
confidence: 99%